A scoping review of system-level mechanisms to prevent children being in out-of-home care. (9th November 2021) - Stabler, Lorna; Evans, Rhiannon; Scourfield, Jonathan; Morgan, Fiona; Weightman, Alison; Willis, Simone; Searchfield, Lydia; Meindl, Mel; Wood, Sophie; Nurmatov, Ulugbek; Kemp, Alison; Forrester, Donald; et al.
Abstract: Identifying which approaches can effectively reduce the need for out-of-home care for children is critically important. Despite the proliferation of different interventions and approaches globally, evidence summaries on this topic are limited. This study is a scoping review using a realist framework to explore what research evidence exists about reducing the number of children and young people in care. Searches of databases and websites were used to identify studies evaluating intervention effect on at least one of the following outcomes: reduction in initial entry to care; increase in family reunification post care. Data extracted from papers included type of study, outcome, type and level of intervention, effect, mechanism and moderator, implementation issues and economic (EMMIE) considerations. Data were coded by: primary outcome; level of intervention (community, policy, organisation, family or child); and type of evidence, using the realist EMMIE framework. This is the first example of a scoping review on any topic using this framework. Evaluated interventions were grouped and analysed according to system-level mechanism. We present the spread of evidence across system-level mechanisms and an overview of how each system-level mechanism might reduce the number of children in care. Implications and gaps are identified. Abstract : There have been many ways attempted to reduce the number of children in care. It is difficult to know which, if any, have successfully achieved this aim, and for which children under which circumstances and in what way. One way of trying to find this out is to do a review of the literature. This review looked for published scientific papers that evaluated whether programmes that aim to reduce the number of children in care worked. The review grouped and summarised papers based on the main way in which the programmes they evaluated aimed to reduce numbers. This overcame the common problem in this literature of programmes that used similar approaches having a few different names. Looking at them based on approach rather than name gave richer information about each type of approach or 'key mechanism'. In total, nine of these 'key mechanisms' were identified, and data are presented which shows how much evidence there is about if they work, how they might work, how they are implemented and cost implications of them.